2014
DOI: 10.5468/ogs.2014.57.5.367
|View full text |Cite
|
Sign up to set email alerts
|

The safety of cesarean myomectomy in women with large myomas

Abstract: ObjectiveTo evaluate the safety of cesarean myomectomy in large myomas sized >5 cm.MethodsOne hundred sixty-five pregnant women with myomas who delivered via cesarean section were identified. Ninety-six women had cesarean section without myomectomy, and 65 women underwent cesarean myomectomy. We compared the maternal characteristics, neonatal weight, myoma types, and operative outcomes between two groups. We further analyzed cesarean myomectomy group according to myoma size. The large myoma was defined as myom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 14 publications
6
36
2
1
Order By: Relevance
“…Studies by Li Hui, et al, Dam hye kwon, et al, Roman et al showed no increase in intraoperative blood loss in types of smaller 3-6cm subserosal and intramural fibroids. [5][6][7] In our study the mean Hb change is not statistically significant in different types of fibroids and we had only one 8cm submucous fibroid which needed an unit of PRBC transfusion. In other studies also, submucous fibroids were encountered in very less numbers (2-13%) and blood loss was not significant compared to other types except the risk of entering the cavity which becomes a risk factor in future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Li Hui, et al, Dam hye kwon, et al, Roman et al showed no increase in intraoperative blood loss in types of smaller 3-6cm subserosal and intramural fibroids. [5][6][7] In our study the mean Hb change is not statistically significant in different types of fibroids and we had only one 8cm submucous fibroid which needed an unit of PRBC transfusion. In other studies also, submucous fibroids were encountered in very less numbers (2-13%) and blood loss was not significant compared to other types except the risk of entering the cavity which becomes a risk factor in future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…About the prophylactic measures, 75% of the women had either vasopressin usage (30) or other Devasularisation methods like Uterine artery ligation, Cornuotubal ligation, uterine artery embolisation, application of tourniquet. 1,2,6 But there is no difference in blood loss between the users and nonusers. In the study by Li Hui, et al, for larger myomas, tourniquet had been used and Adesiyun, et al routinely used Foleys tourniquet around broad ligament and ovarian arteries, Alexander, et al also used tourniquet around the base of broad ligament avoiding the tubes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study could not obtain data on the length of operation, but experience shows that the length of operation will be longer in caesarean myomectomy. Kwon et al 17 conducted a study to compare caesarean myomectomy patients with myomas >5 cm to those with myomas ≤5 cm in terms of preoperative and postoperative haemoglobin changes, length of hospital stay, postoperative fever and length of operation and found no significant difference between the groups. Park et al 5 compared 97 pregnant women who underwent caesarean myomectomy and 60 pregnant women with myomas that had undergone C-section only and identified no complications that were independent from the location of the myoma.…”
Section: Discussionmentioning
confidence: 99%
“…8 This study included 15 term pregnant women with fibroid who had undergone cesarean myomectomy and compared them with control group including 15 pregnant women without fibroid and any other high risk factor matched on basis of gestational age and parity undergoing cesarean section. The outcomes compared were operative time, change in haemoglobin level from pre-operative to postoperative period, post-operative complications, and duration of hospital stay and follow up of patients up to 6 weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%